Why bond market couldn’t thrive in Pakistan - Rehman, Seema; Khilji, Jameel Ahmed (International Journal of Accounting and Economics Studies, 2017)
Fixed income market has recently emerged in Pakistan. Onward 1990, prolusion of government securities paved a way for corporates to come forward with their debt papers and long term yield curve came in to existence by introducing FIB’s in 1992 followed by issuance of first Term Finance Certificates (TFC) in 1995. The TFCs’ coupon rate exhibits a wide range of different fixed and floating coupons related to numerous interest rates containing the discount rate, the Karachi Inter-bank Offer Rate (KIBOR) and Pakistan Investment Bond (PIB) rates. The SBP launched electronic trading platform for fixed income securities on 11th January, 2010 with the intention of improving the functioning and profundity of primary and secondary markets of sovereign bonds. The data available reveals that through this platform, the cumulative trading of sovereign securities touched 66% of the overall trading volume till the end of 2010 relative to 58.0% in January, 2010. In its initial stage, the E-bond platform provided the complete trading of sovereign bonds like T-bills, PIBs and Ijarah Sukuk. The other type of fixed income securities like repo, FRAs and swaps facilitated in subsequent phases.
Keywords: Bond; Coupon Rate; Fib’s; Tfc’s; Kibor.